Społeczno-kulturowe uwarunkowania przeobrażeń struktur organizacyjnych przedsiębiorstw - Lichtarski, Janusz Marek (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2007)
The article presents the review of socio-cultural conditions of organizational structures transformations, from mechanistic to organic ones. Identified factors concern mainly the perception of individual's safety needs, acceptance of heterarchy, individual's flexibility, individuals' learning and development, team co-operation, tolerance, and culture of compromise. The text is based on literature studies, author's own observations and practice, and results of empirical research. (original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2007; nr 1184, s. 385-392